Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1063/1.2769391
|View full text |Cite
|
Sign up to set email alerts
|

Zn vacancy induced room-temperature ferromagnetism in Mn-doped ZnO

Abstract: X-ray absorption fine structure (XAFS) and first-principles calculations were employed to study the structure and ferromagnetism origin of Zn0.97Mn0.03O thin film grown by metal organic chemical vapor deposition. The magnetization measurements indicate that this sample is ferromagnetic at room temperature. The Mn ions are located at the substitutional Zn sites as revealed by the Mn K-edge XAFS spectroscopy. Moreover, the O K-edge XAFS analysis indicated the existence of numerous Zn vacancies. Based on first-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(93 citation statements)
references
References 24 publications
6
86
1
Order By: Relevance
“…1. They are compared to the Mn K-edge spectra recorded for a Zn 0.95 Mn 0.05 O thin film by Pellicer-Porres et al [25] and to the theoretical computations performed by Yan et al [13].…”
Section: Resultsmentioning
confidence: 99%
“…1. They are compared to the Mn K-edge spectra recorded for a Zn 0.95 Mn 0.05 O thin film by Pellicer-Porres et al [25] and to the theoretical computations performed by Yan et al [13].…”
Section: Resultsmentioning
confidence: 99%
“…[28]. So in the present study, the doping level of Mn has etc) is FM at RT [16,29]. As the annealing temperature is same for all the samples (milled for different time), the resultant grain size is expected to be more or less same.…”
Section: Experiments and Data Analysismentioning
confidence: 99%
“…Some type of defects or disorder favors ferromagnetism and others competes with this phenomenon. Reports in favor of Zn vacancy (V Zn ) [8,16], O vacancy (V O ) [17,18] or Zn interstitial (I Zn ) [19] mediated ferromagnetism can be found. It is also found that the defect species involved in inducing ferromagnetism in one ZnO based DMS system may not be effective in similar others [4,7,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] It provides a new way to obtain the DMSs free of magnetic elements. Although several theoretical studies have been done on the magnetic properties of Cu-doped AlN, [20,21] a systematic study on the magnetic mediation of intrinsic vacancies is still absent. Therefore, the origin of ferromagnetism is still unclear and needs further investigations.…”
Section: Introductionmentioning
confidence: 99%